2012
DOI: 10.1007/s10120-012-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of phenotypic expression in undifferentiated-type early gastric adenocarcinomas using mucin core protein and CDX2

Abstract: Background Undifferentiated-type early gastric adenocarcinomas are generally classified into two groups: pure undifferentiated-type adenocarcinomas, which naturally develop as undifferentiated-type without a glandular component; and mixed differentiated/undifferentiated-type adenocarcinomas, which are associated with some vestigial glandular component and presumably develop from differentiated-type adenocarcinoma. The differences in phenotypic expression between these two groups were examined using mucin core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…As previously reported [10][11][12][13][14][15][16], the distributions and positivity rates of MUC5AC and HGM, as well as those of MUC6 and M-GGMC-1, are different. Furthermore, CDX2 is reported to be closely associated with intestinal phenotype expression in human gastric carcinomas [19][20][21] and a more sensitive marker than MUC2 for assessing the presence of intestinal phenotypic expression in gastric adenocarcinomas from the early stage [22]. We therefore employed each of these markers to accurately determine the mucin phenotype of carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported [10][11][12][13][14][15][16], the distributions and positivity rates of MUC5AC and HGM, as well as those of MUC6 and M-GGMC-1, are different. Furthermore, CDX2 is reported to be closely associated with intestinal phenotype expression in human gastric carcinomas [19][20][21] and a more sensitive marker than MUC2 for assessing the presence of intestinal phenotypic expression in gastric adenocarcinomas from the early stage [22]. We therefore employed each of these markers to accurately determine the mucin phenotype of carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the caudal-type homeobox gene Cdx2 encodes a transcription factor that has been found to play an important role in the mammalian intestine [17,18] and which is reported to demonstrate a close relationship to the intestinal phenotype in gastric adenocarcinomas [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse-type neoplasms are considered to be poorly differentiated and arise in normal gastric mucosa [2]. Recently, attempts have been made to more accurately classify gastric adenocarcinomas using immununohistochemical staining [3][4][5]. This method identifies surface gastric and small intestinal mucins.…”
Section: Introductionmentioning
confidence: 99%
“…These findings strongly suggest that phenotype alteration of carcinoma occurs not by the acquisition of a new independent phenotypic expression, but by reduced expression of each phenotype marker during submucosal invasion. Ikarashi et al 33 reported similar phenotype alterations of early undifferentiated-type gastric adenocarcinomas.…”
Section: Discussionmentioning
confidence: 83%